دور المفردات المشتركة بین اللغتین العربیة والمالیزیة في تسھیل تعلم اللغة العربیة كلغة ثانیة = The role of common vocabulary between Arabic and Malay in facilitating learning Arabic as a second language - Mohamad Hairol Kamal, Ahmad Wafi; Chtaibi, Khalid (KLM, IIUM, 2022)
Arabic language is very crucial for Malaysians. Learning it as a second language is a wish of Malaysian students in schools and universities. However, they often encounter difficulties in the learning process due to several factors, including weak educational curricula and a lack of excellent qualified teachers. Therefore, this research comes to explore the role of the shared vocabulary between the Arabic and Malay languages as an encouraging factor that facilitates learning Arabic as a second language in Malaysia. The researchers relied on the shared linguistic stock between the two languages. They adopted the descriptive analytical approach by monitoring, explaining, and analyzing the use of shared vocabulary between the two languages. The questionnaire tool was also used to formulate accurate and specific questions. It was distributed to a sample of the Kulliyyah of Languages and Management students- International Islamic University Malaysia. The researchers came out with results, conclusions, and recommendations to be raised to all those concerned with this subject.